2020
DOI: 10.3390/s20113096
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Metal Oxide-Based Acetone Gas Sensors: A Review

Abstract: Acetone is a well-known volatile organic compound that is widely used in different industrial and domestic areas. However, it can have dangerous effects on human life and health. Thus, the realization of sensitive and selective sensors for recognition of acetone is highly important. Among different gas sensors, resistive gas sensors based on nanostructured metal oxide with high surface area, have been widely reported for successful detection of acetone gas, owing to their high sensitivity, fast dynamics, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(78 citation statements)
references
References 153 publications
(167 reference statements)
0
71
1
Order By: Relevance
“…The desired concentration of acetone vapor is obtained by injecting the Acetone liquid of a particular volume into the chamber. The volume of Acetone in ppm is determined using the equation (15) [33]…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The desired concentration of acetone vapor is obtained by injecting the Acetone liquid of a particular volume into the chamber. The volume of Acetone in ppm is determined using the equation (15) [33]…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Yet, it is explosive and flammable with lower and upper explosive limits of 2.6% and 12.8%, respectively. In addition, it has also been demonstrated that exposure to acetone with more than 173 ppm for a long time can cause several health problems such as headache, narcosis, dizziness, and nausea [6,18–21,28] . In 1971, Pauling et al [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of exposure to the reducing or oxidizing target gases on the conductivity is the reverse of n‐type cases. Beyond n‐type or p‐type metal oxide as a sensing material, combining metal oxides with other metal oxides, noble metals and carbon‐based materials might generate p‐p, n‐p and n‐n type heterojunctions and potentially further enhance the electron mobility (Amiri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%